1999
DOI: 10.1165/ajrcmb.21.1.3570
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Tumor Necrosis Factor (TNF) Receptors p55 and p75 and Interleukin-10 Downregulate TNF- α Activity during the Lung Response to Silica Particles in NMRI Mice

Abstract: We have found reduced activity of tumor necrosis factor (TNF)-alpha accompanying resolving and fibrosing alveolitis induced in NMRI mice by mineral particles (MnO2 and SiO2, respectively), which is in apparent contradiction to the well-recognized proinflammatory and profibrotic activities of this cytokine. The objective of this study was to examine the mechanisms involved in this paradoxical response in NMRI mice. Although lung tissue messenger RNA (mRNA) levels for TNF-alpha were transiently (up to 15 d) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…40,41 The soluble form of the TNF receptor also down-regulates TNF-␣ activity during lung response. 42 Whether the ability of HPAIV to modulate shedding of sTNFR from the surface of monocytes interferes with TNF-␣ action, and thus contributes to pathogenesis, remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 The soluble form of the TNF receptor also down-regulates TNF-␣ activity during lung response. 42 Whether the ability of HPAIV to modulate shedding of sTNFR from the surface of monocytes interferes with TNF-␣ action, and thus contributes to pathogenesis, remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, IL-10 is an anti-inflammatory cytokine, because it downregulates TNFa activity and inhibits long-term IL-6 production (Marshall et al 1996;Huaux et al 1999). By acting as a TH2 cytokine, however, it generally protects against the action of TH1 cytokines (Zhou et al 2004).…”
mentioning
confidence: 99%
“…Th e pro-infl ammatory mediator release may be counteracted by increased IL-10 production, which downregulates TNF-α activity, inhibits long-term IL-6 production (Marshall et al 1996, Huaux et al 1999, blocks NF-κ B activity, and is involved in the regulation of the Janus kinase/signal…”
Section: T T ő K é S Et Almentioning
confidence: 99%
“…Th e spread of pro-infl ammatory events is balanced by the release of anti-infl ammatory cytokines such as interleukin-10 (IL-10), which downregulates TNF-α activity and inhibits long-term interleukin-6 (IL-6) production (Marshall et al 1996, Huaux et al 1999. Indeed, it has been demonstrated that the TNF-α output peaks after 2 -8 h and has usually returned to the baseline by 24 h after radiation (Daigle et al 2001).…”
Section: Introductionmentioning
confidence: 99%